PENGARUH KOMPETENSI, KOMUNIKASI, DAN LINGKUNGAN KERJA FISIK TERHADAP PRODUKTIVITAS KERJA PEGAWAI KANTOR KECAMATAN KRAS - Putri Dwi Astari; Indah Yuni Astuti; Agung Pambudi Mahaputra (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The problem that is the focus of this study is the problem of competence, communication and physical work environment variables on the work productivity of employees at the Kras District Office. The population of employees at the Kras District Office is 39 people. To find out the results of this study, researchers used several methods of validity testing, reliability testing, normality testing, linearity testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression testing, t-test, F-test, R² test. The results of this study obtained a regression of Y = 1.985 + 0.286X1 + 0.174X2 + 0.131X3. Overall, it can be explained that competence, communication and physical work environment have an effect on the productivity of employees at the Kras District Office.